O polityczności Trybunału Konstytucyjnego w kontekście próby jego neutralizowania po wyborach 2015 roku - Zyborowicz, Stanisław (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
Artykuł dotyczy zagadnienia polityczności w kontekście partyjności powoływania sędziów Trybunału Konstytucyjnego. Autor proponuje zastąpienie dotychczasowego paradygmatu tradycyjnego wskazującego na wybory/nominowanie przez Sejm, jako instytucję regulującą kreację. Przedstawia nowy paradygmat oparty na ateńskiej procedurze losowania, które umożliwiłoby powoływanie członków tego organu.

The paper examines the issue of politicization given the context of party affiliation of judges appointed as members of the Constitutional Tribunal. The author suggests that the present traditional paradigm of appointment/selection by the Parliament as a regulatory institution is replaced and presents a new paradigm based on choosing lots as employed in ancient Athens to appoint members of the Constitutional Tribunal.
About the politicization of the Constitutional Tribunal in the context of attempts to neutralize it after the 2015 elections
Keywords: Trybunał Konstytucyjny; polityczność; partyjność; wybory; losowanie; Constitutional Tribunal; politicization; partisanship; elections; draw